DAMPAK KERJASAMA INDONESIA-JAPAN MARITIME FORUM (IJMF) TERHADAP KEAMANAN MARITIM KEPULAUAN NATUNA - Oktavianda, Elga; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to analyze the impact of the Indonesia-Japan Maritime Forum (IJMF) on enhancing maritime security in the Natuna Islands region. The background of this research stems from the increasing security dynamics in the North Natuna Sea caused by illegal fishing activities, territorial violations by foreign vessels, and escalating tensions in the surrounding waters. The study focuses on the period of 2021-2023, covering the dynamics before and after the implementation of the IJMF cooperation. Through the IJMF framework, Indonesia and Japan have strengthened maritime security cooperation and capacity building. This research employs a qualitative approach grounded in K.J. Holsti’s Theory of International Cooperation and the Liberalism perspective, which emphasizes international collaboration among states in addressing common threats. The IJMF cooperation is carried out through various programs such as strengthened collaboration between Bakamla and the Japan Coast Guard, coordination in law enforcement, and infrastructure support including the development of the Marine and Fisheries Center (SKPT) in the Natuna waters. The findings indicate that the IJMF has had a positive impact on maritime security, demonstrated by the decline in illegal fishing incidents from 345 cases (2014-2016) to 167 cases (2021-2023) following the implementation of the cooperation. Positive outcomes have also been experienced by local communities and fishermen in Natuna, as there are no longer foreign fishermen settling in the area, and the establishment of the SKPT in Selat Lampa has improved fishery facilities for local fishermen. Nevertheless, aggressive activities by foreign vessels, particularly from China and Vietnam, remain a challenge to maintaining stability in the North Natuna Sea. Keywords: Indonesia-Japan Maritime Forum (IJMF), Maritime Security, North Natuna Sea, Illegal Fishing, International Cooperation.